Onsite/online: a case study approach pivots to virtual and back with new strategies learned. (2nd August 2022) - Travis, Stephanie
Abstract : The course 'Concepts in modern architecture' is a hybrid between a lecture on the history of modern architecture and an interactive studio. Unlike traditional history courses that discuss many buildings per class, this one delves into a small, highly curated list of projects per session, allowing the students to develop a deep understanding of the architectural concepts used. As such, students form a critical eye to analyse buildings, and work on creative assignments that enforce and communicate these intentions. The course uses the author's IDEA (interaction, define/draw/diagram, engage and assess) methodology as a case study approach. From this 'learn by doing' perspective, students emerge with knowledge that speaks to historical references while utilising their creativity and design skills to assess the works studied. The shift to remote learning due to the COVID-19 pandemic forced this course to shift and evolve, as faculty educators in all disciplines had to rethink their teaching methods. Thus, the online and synchronous version of this course was reimagined in a different environment, using a combination of technological and pedagogical tools that resulted in a strong learning experience with new objectives that engaged the students. Following the adaptation of this course into the virtual sphere, and then back again to the physical classroom, the article reflects on and considers the lessons learned from the experience. There is now a strong virtual course that in the future can continue to reach a broader audience, while the in-person version, which meets regularly back in the studios, has incorporated new techniques that will continue long after the pandemic is over.